2022
DOI: 10.3390/cancers14030740
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Radiotherapy versus Observation for Biochemical Recurrence following Radical Prostatectomy for Prostate Cancer: A Matched Pair Analysis

Abstract: Background: Salvage radiotherapy (SRT) improves oncologic outcomes in prostate cancer (PCa) patients who develop biochemical recurrence (BCR) after radical prostatectomy (RP). However, evidence on hard clinical endpoints is scarce. We compare long-term oncologic outcomes of SRT versus no radiotherapy (noRT) in patients with BCR after RP. Patients and methods: Within a multi-institutional database, we identified patients with BCR after RP between 1989 and 2016 for PCa. Patients with lymph node invasion, with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…A comparison of the patient characteristics in our cohort and three larger studies [4,14,17] revealed a higher proportion of lower Gleason scores and lower median pre-SRT PSA values in our study. These more favorable parameters in our cohort may have a positive impact on the observed OS.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…A comparison of the patient characteristics in our cohort and three larger studies [4,14,17] revealed a higher proportion of lower Gleason scores and lower median pre-SRT PSA values in our study. These more favorable parameters in our cohort may have a positive impact on the observed OS.…”
Section: Discussionsupporting
confidence: 50%
“…In a retrospective study of 501 patients, SRT was associated with a decreased risk of all-cause mortality after a median follow-up of 11.3 years [20]. In addition, a large matched-pair analysis comparing SRT and no SRT confirmed a positive impact of SRT on OS [17]. Our comparison of OS with survival data from an age-matched virtual sample of the general German male population revealed no significant difference, indicating not only improved OS but also normal life expectancy.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These results, obtained for a Caucasian population, show a long‐term benefit of early salvage radiotherapy. The metastasis‐free and OS of the radiotherapy group were no better than that of our surveillance group 13 …”
Section: Discussionmentioning
confidence: 57%
“…The metastasis-free and OS of the radiotherapy group were no better than that of our surveillance group. 13 Among other studies, a study by Stish et al described a cohort of 1,106 patients treated with early salvage radiotherapy, for which the 10-year MFS rate was 80.1% and the 10-year OS rate 77.3%. 14 A study by Pompe et al investigated a cohort of 1,321 patients with biochemical recurrence who received salvage treatment (early salvage radiotherapy, hormone therapy, or chemotherapy).…”
Section: Resultsmentioning
confidence: 99%